The roles of agroclimatic similarity and returns on scale in the demand for mechanization: Insights from Nigeria - Takeshima, Hiroyuki (International Food Policy Research Institute, 2019)
Despite economic transformations and urbanization, declining shares of the workforce employed in the agricultural sector, and gradual growth of agricultural mechanization, production costs in the agricultural sector and food prices remain high in Nigeria relative to those in some of the other developing countries. Understanding how the adoption of mechanical technologies is related to agricultural productivity is, therefore, important for countries like Nigeria. Using farm household data from northern Nigeria as well as var-ious spatial agroclimatic data, this study shows that the adoption of key mechanical technologies in Nigerian agriculture (animal trac-tion, tractors, or both) has been high in areas that are more agro-climatically similar to the locations of agricultural research and de-velopment (R&D) stations, and this effect is heterogeneous, being particularly strong among relatively larger farms. Furthermore, such effects are likely to have been driven by the rise in returns-to-scale in the underlying production function caused by the adoption of these mechanical technologies. Agricultural mechanization, repre-sented here as the switch from manual labor to animal traction and tractors, has been not only raising the average return on scale but also potentially magnifying the effects of productivity-enhancing public-sector R&D on spatial variations in agricultural productivity in countries like Nigeria.